2009
DOI: 10.1007/s00044-009-9162-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on the quantitative structure–toxicity relationships of benzoic acid derivatives in rats via oral LD50

Abstract: Quantitative structure-toxicity relationship (QSTR) studies play an important role in toxicity forecasting, which is widely used in the study of modern compounds. Benzoic acid derivatives are an important type of organic chemicals. Most of them may cause serious public health and environmental problems. The effect of quantum-chemistry parameters on the toxicity of benzoic acid derivatives in rats via oral 50% lethal dose (LD 50 ) was studied by QSTR, and a model to predict the toxicity of benzoic acid derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…(2). Among different studies that have been done on toxicity of benzoic acid derivatives [18][19][20][21][22][23], only Li et al [23] reported QSTR of benzoic acid compounds with MCI in mice via oral LD 50 . Since the subject animal and the route by which the material was administered are important factors in reported values of LD 50 , we compare Tables 3 and 4, which confirm high reliability of Eq.…”
Section: Reliability Of New Methods For a Wide Range Of Benzoic Acid Dmentioning
confidence: 98%
See 1 more Smart Citation
“…(2). Among different studies that have been done on toxicity of benzoic acid derivatives [18][19][20][21][22][23], only Li et al [23] reported QSTR of benzoic acid compounds with MCI in mice via oral LD 50 . Since the subject animal and the route by which the material was administered are important factors in reported values of LD 50 , we compare Tables 3 and 4, which confirm high reliability of Eq.…”
Section: Reliability Of New Methods For a Wide Range Of Benzoic Acid Dmentioning
confidence: 98%
“…Most benzoic acid derivatives may cause public health because they are toxic and hardly degraded by microorganism in the natural environment. For benzoic acid derivatives, various reports of QSAR and QSTR have been published [18][19][20][21][22][23]. For example, Li et al [23] calculated the quantum chemistry parameters with modified molecular connectivity index (MCI) using Visual Basic Program Software.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently found that some relationships can be introduced for prediction of toxicity of benzoic acid and nitroaromatic derivatives through their molecular structures [26][27][28]. A simple correlation has been developed for predicting the toxicity of benzoic acid derivatives in rates via oral lD 50 through the number nitrogen, oxygen, and halogen atoms as well as two correcting functions, which give more reliable results with respect to outputs of training and test sets of QSTR studies of Sun et al [24]. Two simple correlations have also been introduced for predicting the toxicity of benzoic acid derivatives in mice via oral lD 50 .…”
Section: Introductionmentioning
confidence: 98%
“…Thus, differences in the lD 50 toxicity ratings reflect the different routes of exposure as well as toxicity rating can be different for different animals. For example, due to different effects of toxicity of benzoic acid compounds in rats and mice via oral lD 50 , Sun et al [24] and li et al [25] have studied QSTR of benzoic acid derivatives in rats and mice via oral lD 50 , respectively, using complex molecular descriptors. It was recently found that some relationships can be introduced for prediction of toxicity of benzoic acid and nitroaromatic derivatives through their molecular structures [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation